Management principles of osteoporotic fractures. (June 2016) - Gardner, Michael J.; Collinge, Cory
Abstract: Osteoporotic fractures are difficult to manage. They pose a number of difficulties to the surgeon arising from the underlying poor bone stock compromising the intention to achieve optimum fixation. Moreover, the frail elderly patients present with a variety of medical co-morbidities increasing the risk of developing perioperative complications. Despite these recognized challenges, there are currently a number of improving technologies and strategies at the surgeon's disposal to provide more confidence with fracture fixation and maximize the chance of success.